2019
DOI: 10.3390/s19040773
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Sensing Performance of Impedancemetric C2H2 Sensor Using SmFeO3 Thin-Films Prepared by a Polymer Precursor Method

Abstract: A sensitive an impedancemetric acetylene (C2H2) gas sensor device could be fabricated by using perovskite-type SmFeO3 thin-film as a sensor material. The uniform SmFeO3 thin-films were prepared by spin-coating and focusing on the effects of polymer precursor solutions. The prepared precursors and thin-films were characterized by means of thermal analysis, Fourier-transform infrared spectroscopy, ultraviolet–visible spectroscopy, X-ray diffraction analysis, scanning electron microscopy and X-ray photoelectron s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 30 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…In the last decade, standard air quality inspection stations and small gas sensors, such as infrared dots, catalytic beads, and photoionized and metal oxide semiconducting (MOS) sensors, have been the subject of many studies [3]. Recently, a polarization-insensitive design of a hybrid plasmonic waveguide to detect methane gas [4], using SmFeO 3 material to detect acetylene, has also been reported [5]. However, for applications to protect human health on the go, gas sensors must be miniaturized, sensitivity must be increased, and power consumption and cost must be reduced.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, standard air quality inspection stations and small gas sensors, such as infrared dots, catalytic beads, and photoionized and metal oxide semiconducting (MOS) sensors, have been the subject of many studies [3]. Recently, a polarization-insensitive design of a hybrid plasmonic waveguide to detect methane gas [4], using SmFeO 3 material to detect acetylene, has also been reported [5]. However, for applications to protect human health on the go, gas sensors must be miniaturized, sensitivity must be increased, and power consumption and cost must be reduced.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with these large-scale detection instruments, the gas sensor has advantages of small size, simple structure, and good performance, and is a new DGA technology with great application potential. A wide variety of gas sensors, including semiconductors and electrochemical, have been extensively studied for their acetylene-sensitive properties over the past few decades [ 8 , 22 , 23 , 24 , 25 , 26 , 27 ]. For example, Barsan et al studied the sensitivity of the Ag-loaded LaFeO 3 semiconductor to C 2 H 2 gas, and they found that the response and selectivity of the LaFeO 3 sensor to acetylene were optimal when the Ag loading was 0.1 wt% [ 28 ].…”
Section: Introductionmentioning
confidence: 99%